New knowledge on divergent domestication traits in swamp and river buffalo - CGIAR Research Program on Livestock (2020)
Journal article on understanding divergent domestication traits from the whole-genome sequencing of swamp- and river-buffalo. Next users include population geneticists, bioinformaticians, and animal breeders.